2018
DOI: 10.1029/2018ja025705
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Freshly Generated Equatorial Spread F (F‐ESF) Irregularities on Quiet and Disturbed Days

Abstract: We examined the seasonal and solar flux dependence of the occurrence of freshly generated intermediate scale (100 m to few km) equatorial spread F (ESF) irregularities during magnetically quiet (Q) and disturbed (D) periods. We utilized long‐term (1992–2006 and 2013–2015) amplitude scintillation data on a 251 MHz signal recorded at Tirunelveli (dip lat. 1.5°N ). Also, ionosonde data (1990–2003) recorded at Trivandrum (dip lat. 0.5°N) are used. The presence of fresh ESF (F‐ESF) is identified using the maximum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Day‐to‐day variation in the occurrence of ESF irregularities and their characteristics and ambient F region parameters like electron density, electric field, conductivities, and height are well reported in many earlier studies (Burke et al, ; Gurram et al, ; Kakad, Tiwari, & Pant, ; Li et al, ; Nishioka et al, ; Yamazaki et al, ). Apart from day‐to‐day variations, these parameters are also affected by the modulated neutral winds resulting from the enhanced Joule energies at high latitudes and prompt penetration electric fields during periods of geomagnetic storms (Bhattacharyya et al, ; Kakad et al, ; ; Kikuchi et al, ).…”
Section: Resultssupporting
confidence: 71%
“…Day‐to‐day variation in the occurrence of ESF irregularities and their characteristics and ambient F region parameters like electron density, electric field, conductivities, and height are well reported in many earlier studies (Burke et al, ; Gurram et al, ; Kakad, Tiwari, & Pant, ; Li et al, ; Nishioka et al, ; Yamazaki et al, ). Apart from day‐to‐day variations, these parameters are also affected by the modulated neutral winds resulting from the enhanced Joule energies at high latitudes and prompt penetration electric fields during periods of geomagnetic storms (Bhattacharyya et al, ; Kakad et al, ; ; Kikuchi et al, ).…”
Section: Resultssupporting
confidence: 71%
“…We noticed that days with FESF produce more moderate-strong scintillations during the night as compared to days with drifted-in ESF. Recently, Gurram et al (2018) have reported active phase durations of the FESF observed at dip equatorial station Tirunelveli. However, in their study, they did not investigate the solar flux and geomagnetic activity dependence of active phase of FESF, which we have examined here.…”
Section: Discussionmentioning
confidence: 99%
“…We do not have much information about the duration of the perturbation electric field of EPBs. Recently, Gurram et al (2018) for the first time estimated the average duration of active phase of EPBs drifting over Tirunelveli using long-term VHF scintillation observations. In their study, efforts have been made to quantify the active phase duration, and it is reported that the perturbation electric field linked with the FESF survives for more time on magnetically disturbed days (D-days) as compared to that on Q-days.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations